Oestrogen Receptor Alpha in Myocyte Maintains Muscle Regeneration in Duchenne Muscular Dystrophy - Xiaofei Huang; Sijia Li; Huna Wang; Lei Zhao; Xihua Li; Shusheng Fan; Wanting Hu; Haowei Tong; Guangyao Guo; Dengqiu Xu; Luyong Zhang; Zhenzhou Jiang; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Oestrogen receptor alpha (ERα) plays an important role in maintaining mitochondrial function and regulating metabolism in skeletal muscle. However, its alterations and potential mechanisms in Duchenne muscular dystrophy (DMD) remain incompletely understood. In this study, we demonstrated the protective role of ERα in myocyte for skeletal muscle regeneration in mdx mice and explored the therapeutic effects of oestrogen receptor modulators on DMD. Methods DMD patients' biopsies were obtained for histological analysis to explore the expression of ERα. The phenotype of muscle was analysed by histology and molecular biology. The therapeutical effect of different oestrogen receptor modulators was examined in mdx mice treated with fulvestrant (FVT, 20 mg/kg once a week) or oestradiol (E2, 1 mg/kg per day) for 4 weeks. The protective effect of ERα was performed on mdx mice after conditional knockout of ERα in skeletal muscle (ERαmKO mdx mice). Evidence of activation of ERα/oestrogen‐related receptor alpha (ERRα)/myogenic differentiation 1 (MyoD) signalling pathway was inspected in the primary myoblasts isolated from mice, and C2C12 cells received intervention with E2/FVT/Esr1‐siRNA/Esrra overexpression plasmid. Results The ERα expression was increased in DMD patients' triceps (p < 0.05) and mdx mice muscles (p < 0.05). FVT reduced ERα levels in the mdx mice muscles (p < 0.01) but had no significant effect on skeletal muscle regeneration on mdx mice. Compared with mdx mice, E2 reduced the levels of creatine kinase (CK) and lactic dehydrogenase (LDH) (p < 0.001) in serum, enhanced skeletal muscle function, alleviated skeletal muscle atrophy and fibre loss and upregulated the expression of ERα in GAS (p < 0.001) and TA (p < 0.05). The myogenic factors such as myosin heavy chain (MyHC, p < 0.001), myogenin (MyoG, p < 0.05), MyoD (p < 0.05) and ERRα (p < 0.001) were increased in mdx mice GAS with E2. But E2 had no effect on ERαmKO mdx mice. The primary myoblasts and C2C12 were treated with E2 displayed an increased‐on myocyte fusion index (p < 0.05), ERα MyoD and ERRα expressions (p < 0.05). The myocytes' fusion index (p < 0.05) and ERα, MyoD and ERRα expression (p < 0.05) were decreased in si‐Esr1‐transfected C2C12 cells and increased in OE‐Esrra‐transfected C2C12 cells. Conclusion We demonstrated that ERα in myocyte exerted a protective effect on skeletal muscle regeneration in DMD patients and mdx mice through the ERα‐ERRα‐MyoD pathway, which has potential implications for DMD therapy strategies.